Secure Data Transmission Using Trust Based Multi Objective Gazelle Optimization Algorithm for VLC-VANET - Begum, Shaeista; Patil, Nagaraj B. (2023 3rd International Conference on Mobile Networks and Wireless Communications (ICMNWC), 2023)
VANET, belonging to the subclass of MANET, is widely recognized as a highly promising approach. However, it distinguishes itself from conventional ad hoc networks due to its unique characteristics and behavior. Implementing secure broadcasting can be challenging due to factors like limited resources, the dynamic nature of networks, and trust management. To overcome those issues, the trust-based Multi-Objective-Gazelle Optimization Algorithm (TMO-GOA) method is used in this paper to offer great security for the data packets and stop malicious attacks. The secure clustering-based routing protocol uses the TMO-GOA approach, which is introduced to perform quality routing through VLC-VANET. Then the proposed approach benefits by attaining an optimal routing path between source vehicles and the roadside units at the destination. The enhancement of TMO-GOA takes place utilizing distance among the neighboring nodes, the distance between destination and cluster head, residual energy, and the CH balancing factor. The utilization of optimal fitness functions helps overcome issues like higher energy consumption, delay, and node failure. The obtained results show that the proposed TMO-GOA has attained comparatively better outcomes compared with former approaches according to parameters like packet delay, packet drop, energy consumption, and packet delivery ratio (PDR). These outcomes prove the efficacy of the suggested approach by attaining a lower energy consumption of 3.2 mJ rather than the former approaches of 10 mJ, 8.2 mJ, and 4.8 mJ, respectively.